2014
DOI: 10.1111/jicd.12079
|View full text |Cite
|
Sign up to set email alerts
|

Influence of surface free energy of denture base and liner materials onCandida albicansbiofilms

Abstract: Increases in SFE from pellicle-coating leads to robust mature C. albicans biofilms on both denture materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 22 publications
(106 reference statements)
0
28
0
Order By: Relevance
“…Several researchers suggested that the surface roughness of the materials is the most important factor affecting the adhesion of C. albicans . Light and electron microscopy studies reveal that initial adhesion of microorganisms generally begins in the pits and fissures of rough surfaces, which are known to provide protection against shear forces and provide time for irreversible adhesion of microbial cells to the surface.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Several researchers suggested that the surface roughness of the materials is the most important factor affecting the adhesion of C. albicans . Light and electron microscopy studies reveal that initial adhesion of microorganisms generally begins in the pits and fissures of rough surfaces, which are known to provide protection against shear forces and provide time for irreversible adhesion of microbial cells to the surface.…”
Section: Discussionmentioning
confidence: 99%
“…Surface free energy is another factor affecting initial microbial adhesion and biofilm formation on material surfaces . In principle, materials with lower surface free energy (hydrophobic) exhibit a higher water contact angle .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations